Technical Assistance in Determining the Heat Adequacy Number (F0) in the Sterilization Process of Packaged Rendang for Rendang Business Actors IKABOGA in Padang City - Syukri, Daimon; Bahar, Rini; Jessica, Adhitya; Novelina, Novelina; Dini Hari, Purnama; Meuthia Fiana, Risa; Anggraini, Tuty; Mislaini, Mislaini; Amaliyah Tarumiyo, Aurelia; Azzahra, Yasmin; Aidila Fitria, Eddwina (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2024)
This community service activity aims to assist rendang business actors who are members of IKABOGA in Padang City in determining the heat adequacy number (F0) in the sterilization process of packaged rendang. Determining the correct F0 number is very important to ensure food safety, extend product shelf life, and maintain rendang quality. Assistance methods include theoretical training, F0 calculation simulations, sterilization practices, and preparation of Standard Operating Procedures (SOPs). The results of the activity showed an increase in business actors' understanding of the F0 concept, as well as the implementation of a more measurable and safe sterilization process. Laboratory tests showed that rendang products sterilized with the appropriate F0 value were proven to be free from pathogenic microorganisms, while the quality of taste, texture, and aroma were maintained. This activity is expected to help business actors improve product quality and competitiveness, and comply with applicable food safety standards.